The Effects of Examinee Motivation on Multiple-Choice Item Parameter Estimates - van Barneveld, Christina (Alberta Journal of Educational Research, 2003)
The purpose of this study was to examine the effects of false assumption regarding the motivation of examinees on item calibration and test construction. A simulation study was conducted using data generated using two models of item responses (the 3-parameter logistic item response model alone, and in combination with Wise's Examinee Persistence model (1996a)). Items were calibrated using a Bayesian method. Results clearly document the effect of low motivation on item parameter estimates. For the conditions studied, the item parameter estimates based on responses from poorly motivated examinees were biased and more variable than estimates based on responses from examinees who behaved according to the three-parameter logistic model.